Varied clinical presentation of Meckel’s diverticulum in pediatric population - Pramod, S; Meghan, G S; Sridhar, G (Indian Journal of Child Health, 2019)
Background: Meckel’s diverticulum (MD) is one of the most prevalent congenital abnormalities of the small intestine. Due to its wide-ranging presentations, it often becomes a challenge to diagnose it. Objective: The objective of the study is to analyze varied clinical manifestations of MD in children and their outcomes. Materials and Methods: This was a retrospective study of children diagnosed with MD in the Department of Pediatric Surgery, Medical College of Karnataka from January 2015 to January 2019. A total of 13 patients (10 male and 3 female) aged 1 month–15 years with a diagnosis of MD were included in the study. Their demographic and clinical parameters, investigation, and histopathological findings along with the surgical interventions were collected and analyzed. Results: Patients were presented with varied clinical features such as intestinal obstruction (30.76%), perforated MD (15.38%), diverticulitis (15.38%), gastrointestinal bleed (7.69%), patent vitellointestinal duct (7.69%), and incidental (23.07%). All the cases were investigated and underwent treatment. The most common post-operative complication was wound infection in 2 children which were treated conservatively. Conclusion: A pre-operative diagnosis of complicated MD may be challenging because of the overlapping clinical and imaging features of the other acute surgical and inflammatory conditions of the abdomen. Therefore it is necessary to maintain a high incidence of suspicious in the pediatric age group.